Linear and star-shaped extended di- and tristyrylbenzenes: synthesis, characterization and optical response to acid and metal ions - Zhang, Hao; Kotlear, Eugen A.; Kushida, Soh; Maier, Steffen; Rominger, Frank; Freudenberg, Jan; Bunz, Uwe H. F. (Chemistry - a European journal, 2020)
Two linear 1,4-distyrylbenzenes and five star-shaped 1,3,5-tristyrylbenzene derivatives (L2a and L2b, Y0-Y3 and YNBu) were synthesized and spectroscopically characterized. The photophysical properties, optical response to acid and metal ions were investigated. Upon backbone extension of linear distyrylbenzenes or the introduction of dibutylanilines, the electronic spectra are redshifted. Incorporation of electron-deficient pyridyl units does not significantly affect the optical properties. Variation of the number of pyridine rings and substitution pattern tune the fluorescence response to acids and metal ions. The novel arenes discriminate Al3+, Mn2+, Fe3+, Fe2+, Cd2+, Ag+ and Hg2+.